Katerina Galani, British Shipping in the Mediterranean during the Napoleonic Wars. The Untold Story of a Successful Adaptation, Leiden – Βοστώνη, Brill, 2017 - ΜΑΝΤΟΥΒΑΛΟΣ IΚΑΡΟΣ (Μνήμων, 2024)
Δεν διατίθεται περίληψη